Selection and validation of RT-qPCR reference genes for multi-tissue gene expression normalization in two honeybee subspecies across post-emergence developmental stages - Liu, Xuanpeng; Yang, Ting; Li, Jilian; Ma, Chuan (BMC genomics, 2025)
Background The western honeybee ( Apis mellifera ) represents a pivotal model organism for investigating social organization and phenotypic plasticity. Behavioral specialization in worker bees induces tissue-specific molecular adaptations, particularly in sensory and secretory tissues. Although real-time quantitative PCR (RT-qPCR) has been extensively employed to quantify gene expression dynamics in these tissues, systematic evaluation of optimal reference genes for RT-qPCR data normalization remains undressed. Results We systematically assessed nine candidate reference genes across three tissues (antennae, hypopharyngeal glands, and brains) in adult honeybees at three developmental stages (newly emerged bees, nurses, and foragers) from two subspecies ( A. m. ligustica and A. m. carnica ). Using five statistical algorithms (geNorm, NormFinder, BestKeeper, ΔC T method, and RefFinder), we identified ADP-ribosylation factor 1 ( arf1 ) as the most stable reference gene across all experimental conditions, followed by ribosomal protein L32 ( rpL32 ). Their stability was confirmed by experimental validation through normalization of major royal jelly protein 2 ( mrjp2 ) expression patterns. Notably, three conventional housekeeping genes ( α-tubulin , glyceraldehyde-3-phosphate dehydrogenase , and β-actin ) displayed consistently poor stability, disqualifying their application in quantitative analyses under these experimental conditions. Conclusions Our findings provide validated reference genes for precise quantification of tissue-specific gene expression patterns during adult honeybee development. These reference genes facilitate identification of candidate genes associated with honeybee development, social behavior, and productivity traits.